The addiction behavior of short-form video app TikTok: The information quality and system quality perspective - Qin, Yao; Omar, Bahiyah; Musetti, Alessandro (Frontiers in Psychology, 2022)
TikTok has one of the most advanced algorithm systems and is the most addictive as compared to other social media platforms. While research on social media addiction is abundant, we know much less about how the TikTok information system environment affects users’ internal states of enjoyment, concentration, and time distortion (which scholars define as the flow experience), which in turn influences their addiction behavior. To fill this gap, this study collects responses from 659 adolescents in China aged between 10 and 19 years old, and the data is then analyzed using Partial Least Square (PLS). We find that the system quality has a stronger influence than information quality in determining adolescents’ experience with TikTok, and that the flow experience has significant direct and indirect effects on TikTok addiction behavior. Notably, this study finds that TikTok addiction is determined by users’ mental concentration on the medium and its content. Several theoretical insights from the stimulus-organism-response (S-O-R) model and the flow theory are used to explain the findings.